Implementasi Media Tugu Budaya Berbasis Model Problem Based Learning dalam Upaya Peningkatan Hasil Belajar Keberagaman Budaya pada Peserta Didik Kelas III - Pratiwi, Evi; Purwati, Panca Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of learning models and media that are less innovative can affect students' understanding of the material being taught. Students' learning outcomes have not yet reached the criteria for achieving learning objectives (KKTP) due to students' difficulties in understanding and remembering material related to cultural diversity. The aim of this research is to describe the implementation of cultural monument media based on the problem based learning model in an effort to improve the learning outcomes of class III students on cultural diversity material. The subjects in this research were 27 students in class III of SD Negeri Ngaliyan 05, Semarang City, consisting of 16 male students and 11 female students. This research uses qualitative descriptive analysis. The results of the research show that the application of cultural monument media based on the problem based learning model in class III of SD Negeri Ngaliyan 05, Semarang city provides students with an understanding of cultural diversity material and has an effect on improving learning outcomes which can be seen from the average posttest score which is higher than the results. pretest score with an increase of 12.59.